A micro-level analysis of commuting and urban land using the Simpson's index and socio-demographic factors. (August 2022) - Momeni, Ehsan; Antipova, Anzhelika
Abstract: This study explores the association between urban form, socio-demographics, and travel behavior for 1990, 2000, and 2010 in Shelby County, Tennessee, at a micro-level using U.S. Census tracts capturing active and passive transportation modes. We used bivariate correlations between land use and land cover mix (estimated separately by Simpson's index), population, race, age, education, and commuting modes. Major findings indicate that land use mix is positively related to public transportation use while the land cover mix is negatively related; the opposite is found for both diversity measures and working from home. Greater land cover diversity discourages walking and biking and encourages car commuting; Blacks are the majority who use public transportation; older travelers are more likely to use transportation alternatives; higher-educated people tend to work from home or commute by bike. This study helps city planners in designing sustainable cities and increasing active modes use. Understanding travel patterns may help policymakers to control local/regional problems like increasing traffic congestions and emissions due to a modal shift in commuting to a private car during a COVID-19 pandemic, as well as develop strategies for encouraging active modes and public transport use in the post-COVID-19 world. Highlights: The share of developed land use in Shelby County has increased during the past three years to meet the demand for housing and jobs for the growing population. Land use mix and land cover mix are associated significantly with the use of public transportation and working at home. Blacks constitute the majority who use public transportation. Older travelers are more likely to use alternative transportation modes. Higher-educated people are more likely to work at home or use a bike for commuting.